2015
DOI: 10.1002/cbic.201500357
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective Modulation of the RhlR Quorum Sensing Receptor by Using Non‐native Ligands: An Emerging Target for Virulence Control in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa uses N-acylated L-homoserine lactone signals and a triumvirate of LuxR-type receptor proteins – LasR, RhlR, and QscR – for quorum sensing (QS). Each of these receptors can contribute to QS activation or repression, and thereby, the control of myriad virulence phenotypes in this pathogen. LasR has traditionally been considered at the top of the QS receptor hierarchy in P. aeruginosa; however, recent reports suggest that RhlR plays a more prominent role in infection than originally predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 64 publications
1
72
0
Order By: Relevance
“…We thus assembled a group of small molecules representing some of the most potent synthetic inhibitors of P. aeruginosa QS circuits known. These included: the LasR antagonist 1 , introduced above (Müh et al, 2006, Moore et al, 2015); the RhlR antagonist 2 , reported by our laboratory (Welsh et al, 2015, Eibergen et al, 2015); and the PqsR antagonist 4 , reported by Rahme and coworkers (Figure 1B) (Starkey et al, 2014). Each compound is capable of inhibiting the activity of its target receptor by ≥85% in reporter gene assays (see Figure S2 and the above references for each compound).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We thus assembled a group of small molecules representing some of the most potent synthetic inhibitors of P. aeruginosa QS circuits known. These included: the LasR antagonist 1 , introduced above (Müh et al, 2006, Moore et al, 2015); the RhlR antagonist 2 , reported by our laboratory (Welsh et al, 2015, Eibergen et al, 2015); and the PqsR antagonist 4 , reported by Rahme and coworkers (Figure 1B) (Starkey et al, 2014). Each compound is capable of inhibiting the activity of its target receptor by ≥85% in reporter gene assays (see Figure S2 and the above references for each compound).…”
Section: Resultsmentioning
confidence: 90%
“…Arrows with solid lines indicate direct, positive regulation while arrows with dashed lines indicate positive regulation by indirect or unknown mechanisms. Small molecule QS probes used in this study include the LasR antagonist 1 (V-06-018) (Müh et al, 2006, Moore et al, 2015), the RhlR antagonist 2 (E22) (Welsh et al, 2015, Eibergen et al, 2015), the RhlR agonist 3 (S4) (Welsh et al, 2015), and the PqsR antagonist 4 (M64) (Starkey et al, 2014). …”
Section: Figurementioning
confidence: 99%
“…The BHL-derived library can be divided into two groups: ( 1 ) compounds with modified tails and native lactone head groups (i.e., the tail library), and ( 2 ) compounds with modified head groups and native butanoyl tails (i.e., the head library). The tail library compounds can be further divided into three subsets based on structural similarity to either BHL or our two previously reported potent RhlR activators 2 and 3 (28) . The first subset of compounds ( 4 – 11 ) retains the short-chain alkyl characteristics of native ligand BHL, with compounds designed to probe both tail length and alkyl substitution on the tail.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 21 and 22 were previously characterized and included for comparison in the current study (28) .…”
Section: Figurementioning
confidence: 99%
“…This study only failed to reveal ligands that selectively activate AbaR and/or selectively inhibit LasR. Nevertheless, other than some of our past studies, 2629 the development of ligands with LuxR-type receptor selectivity remains largely unchartered; thus, the discovery of these activity profiles for these ligands in AbaR and LasR is significant. These ligands could be utilized in a range of interesting experiments of both fundamental and direct clinical interest to test the impact of AbaR and LasR modulation in mixed cultures of A. baumannii and P. aeruginosa —mixtures that are relevant to infection populations.…”
Section: Resultsmentioning
confidence: 85%